Risk of Recurrence After Surviving Severe Sepsis: A Matched Cohort Study. Issue 10 (October 2016) - Shen, Hsiu-Nien; Lu, Chin-Li; Yang, Hsi-Hsing
Abstract : Objectives: To examine the risk of recurrence in adults who survived first-episode severe sepsis for at least 3 months. Design: A matched cohort study. Setting: Inpatient claims data from Taiwan's National Health Insurance Research Database. Subjects: We analyzed 10, 818 adults who survived first-episode severe sepsis without recurrence for at least 3 months in 2000 (SS group; mean age, 62.7 yr; men, 54.7%) and a group of age/sex-matched (1:1) population controls who had no prior history of severe sepsis. All subjects were followed from the study entry to the occurrence of end-point, death, or until December 31, 2008, whichever date came first. Interventions: None. Measurements and Main Results: Primary end-point was severe sepsis that occurred after January 1, 2001 (the study entry). Relative risk of the end-point was assessed using competing risk regression model. During the follow-up period, severe sepsis and death occurred in 35.0% and 26.5% of SS group and in 4.3% and 18.6% of controls, respectively, representing a covariate-adjusted sub–hazard ratio of 8.89 (95% CI, 8.04–9.83) for the risk of recurrence. In stratified analysis by patient characteristics, the sub–hazard ratios ranged from 7.74 in rural area residents to 23.17 in young adults. In subgroup analysis by first-episode infection sites in SS group, the sub–hazard ratios ranged from 4.82 in intra-abdominal infection to 9.99 in urinary tract infection. Conclusions: Risk of recurrence after surviving severe sepsis is substantial regardless of patient characteristics or infection sites. Further research is necessary to find underlying mechanisms for the high risk of recurrence in these patients. Abstract : Supplemental Digital Content is available in the text.